Effects of Xylanase and monensin sodium on broiler chick growth performance - Dostal, Elyse N.; Delfelder, C.J.; Beyer, R. Scott; Stark, Charles R.; Evans, C.E.; Yoder, Ashton D.; Jones, Cassandra K. (My University, 2017)
Consumers these days want limited use of antimicrobials in poultry feed. One potential alternative to replace antimicrobials is to use exogenous xylanase. It is known that this enzyme will improve nutrient digestibility in higher fiber diets, but its ability to replace an antimicrobial is unknown. Therefore, the objective of this experiment was to evaluate if xylanase can replace monensin sodium to improve nutrient digestibility and if the impact differs based on the fiber level of the diet. A total of 216 Cobb 1-d-old chicks (6 birds/cage and 6 cages/treatment) were fed 1 of 6 dietary treatments consisting of a corn- or wheat-based diet supplemented with either 0.10 g/kg monensin sodium (Coban 90; Elanco Animal Health, Greenfield, IN) or 16,000 betaxylanase units/kg beta 1-4, endo-xylanase enzyme (Econase XT; AB Vista, Marlborough, UK). The birds were fed ad libidum in battery cages for 21 days in length. The treatments used were: 1) Corn-based with no monensin sodium or xylanase; 2) wheat-based with no monensin sodium or xylanase; 3) corn-based with monensin sodium but no xylanase; 4) wheat-based with monensin sodium but no xylanase; 5) corn-based with xylanase but no monensin sodium; 6) wheat-based with xylanase but no monensin sodium. Weekly the birds body weights and feed intakes per cage were reported to determine BW gain, total feed intake, and FCR. Data were analyzed using the GLIMMIX procedure of SAS with cage as the experimental unit and treatment as the fixed effect. We found the treatment (P < 0.01) final BW, feed intake, and FCR. Final body weights of the cages at day 21 ranged from 848.5 g to 940.4 g. While feed intake at day 21 ranged from 54.0 g to 59.6 g; with the corn-based control diet had improved (P < 0.05) FCR compared to the wheat-based control diet. In corn-based diets, neither the monensin sodium nor the xylanase improved (P > 0.05) FCR compared to the corn-based control. In wheat-based diets, xylanase (P < 0.05) but not monensin sodium (P > 0.05) improved FCR compared to the wheat-based control. In conclusion, this research suggests that xylanase improves carbohydrate digestibility in wheat-based diets, restoring FCR to that of corn-based diets. However, there was limited impact of feeding an antimicrobial in this setting.
Keywords: Spring 2017